A comparative study on the removal of dimethyl sulfoxide from water using microbubbles and millibubbles of ozone. (April 2021) - Jabesa, Abdisa; Ghosh, Pallab
Graphical abstract: Highlights: Ozone microbubbles were more efficient for TOC removal than the millibubbles. Higher volumetric mass transfer coefficient was obtained by the microbubbles. High ozone utilization efficiency was achieved by the ozone microbubbles. The degradation of DMSO to methane sulfonic acid was achieved via two paths. Stoichiometric ratio of ozone consumed to the DMSO removed was computed. Abstract: Ozone-based microbubble-aided technology has been gaining popularity as a new potential alternative method for the oxidation of organic pollutants present in water/wastewater. In this work, the potential of the ozone microbubbles (OMBs) for the oxidation of dimethyl sulfoxide (DMSO) was investigated, and the results were compared with those of the conventional ozone millibubbles (OMLBs). Keeping constant other operational parameters, the OMLBs needed a longer time for complete removal of DMSO, and hence a higher consumption of ozone took place. Therefore, a higher stoichiometric ratios of ozone consumed to the DMSO removed was obtained for the OMLBs. Higher ozone utilization efficiencies were observed for the OMBs (i.e., 65–79 %) than the OMLBs (i.e., 21–48 %). Coupling of H2 O2 with the ozonation systems improved the oxidation of DMSO by enhancing the formation of · OH. Conversely, a large dosage of H2 O2 had a negative effect. The degradation of DMSO to methane sulfonic acid (MSA) was achieved via two paths (i.e., direct conversion to MSA by the reaction with · OH, and a two-stage conversion via the formation of DMSO2 by molecular ozone, followed by further oxidation of DMSO2 to MSA by the ·OH). In terms of the TOC removal efficiency, the effectiveness was in the following order: OMLBs < OMLBs/H2 O2 < OMBs < OMBs/H2 O2 . Oxidation of DMSO by ozone followed an overall second-order kinetics for the OMBs, and first-order kinetics for the OMLB system. Higher enhancement factor and volumetric mass transfer coefficient were obtained for the OMBs as compared to OMLBs.